Internal Migration, Exclusionary Politics and Crises of Nation-Building in Nigeria - YEMISI, Olawale (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
The article examines the crises of nation-building in Nigeria from the perspective of internal migration, exclusionary discourses and politics. Population movement has been a constant feature of human interactions and relations. One of the major constant features of internal migration interpretation has been its continuous intersection with economic considerations and social security. However, in Nigeria, the internal migration of different ethnic groups within the territories has witnessed the interplay of exclusionary discourses and politics or a series of policies and debates directed toward profiling the migrant population to achieve certain objectives. In Nigeria, the Igbo migrants and politics of Lagos State and the Fulani herders’ pastoralists fit into the broad spectrum of this thesis. However, the task of nation-building in Nigeria is a continuous process that involves a careful dialogue on matters that border on national questions. Hence, the reality of the Nigerian nation-building project is the crisis of managing various ethnic and religious identities towards national integration. The article builds on these two cases to shed light on understanding ethnic tension, suspicion and its implications on nation-building through the prism of internal migration. The article relies on secondary data sources.